No association between candidate genes for color determination and color phenotype in Hierophis viridiflavus, and characterization of a contact zone. (16th January 2021) - Senczuk, Gabriele; Gramolini, Laura; Avella, Ignazio; Mori, Emiliano; Menchetti, Mattia; Aloise, Gaetano; Castiglia, Riccardo
Abstract: Genetic and phenotypic differentiation in allopatric conditions can be explained either by neutral phenomena or adaptative processes driven by selection. In reptiles, coloration can affect aspects directly related to their survival, representing a classical character under selection. In this context, secondary contact areas are natural laboratory to understand evolutionary processes underlying genetic permeability, especially when populations differ in phenotypic traits such as coloration. The western whip snake Hierophis viridiflavus presents two divergent mitochondrial clades, characterized by the presence of one of two main color phenotypes, namely one with black and yellow stripes and a fully melanic one. Here, we investigated whether melanogenesis‐linked genes are determinant of the chromatic differences observed across the phenotypic variation of the species. In addition, we used a multilocus dataset, including 134 original ND4 sequences, to better define the overall genetic structure and to provide a characterization of a contact zone identified in Central Italy by estimating the amount of nuclear gene exchange. While we found no evidence supporting a direct association between target genes and coloration, a non‐synonymous substitution polymorphism, at high frequency, was detected in the β melanocyte‐stimulating hormone whose possible function has been discussed. Concerning the genetic structure, both mtDNA and nuDNA were partly concordant indicating introgression events occurring at the contact zone. When we measured the nuclear gene flow, we found a significant amount of gene exchange, mainly guided from one clade to the other, that is, asymmetric. These results might suggest the presence of ecological and/or behavioral processes driving the observed directional gene flow. Abstract :